Peran Halal Center Dalam Memajukan Ekonomi Halal Berkelanjutan Di Sektor Industri Halal - Husein Lubis, Rahmat (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2021)
This research aims to find out the role of halal centers in boosting the halal economy in the Indonesian halal industrial sector. This type of research is descriptive qualitative research. Descriptive qualitative research is research that examines several sources. Where the research sources used are several sources such as books, scientific journals, encyclopedias, literature, works of scientists, as well as government agency websites that are related to this research. The object of research in this research is writing or text related to the current development of the Indonesian halal industry. The results of this research show that the role of the halal center is very influential on the development process of the halal industry in Indonesia. Where it can be seen that in 2020 the total number of halal certification registrations was 11,103 and in 2023 the total number of halal certification registrations was 155,451. Then in data from The State of the Global Islamic Economy Report 2022, Indonesia managed to rank 4th in the world with halal product consumer coverage amounting to 11.34% of global halal expenditure.